Low Cost, Recyclable and Magnetic Moringa Oleifera Leaves for Chromium(VI) Removal From Water - Masekela, Daniel; Yusuf, Tunde L.; Hintsho-Mbita, Nomso C.; Mabuba, Nonhlangabezo (Frontiers in Water, 2022)
Chromium(VI) a heavy metal by nature, is one of the most toxic metals in the environment. We recently reported functionalised Moringa Oleifera (FMO) leaves as a low cost and efficient adsorbent for the removal of Cr(VI) and bacterial from water, as a continuation, we report the incorporation of magnetic nanoparticles(Fe3O4) with previously studied FMO for Cr(VI) removal from aqueous solution. Iron oxide due to its magnetic properties has been shown to assist in the recovery of its adsorbents. In this study, in-situ co-precipitation synthesis of iron nanoparticles onto FMO was employed. During chemical precipitation, the iron precipitate tends to cover the FMO thus forming some outer-shell coating of magnetite on the surface of FMO. The Fe3O4/FMO was characterized using XRD, FTIR, SEM, BET, TGA and Zeta potential. FTIR results showed a new developed intense peak at 685.6 cm-1 for Fe-O stretching, indicating successful incorporation of Fe3O4 nanoparticles onto FMO. Powder XRD was further use to confirm the formation and further indicated that the structure of FMO was still intact even after the Fe3O4 incorporation. The adsorption conditions such as pH, dosage, time and concentration were optimized to 2, 0.15 g, 25 min and 20 mg/L, respectively. The adsorbent was selective towards Cr(VI) since 99 % was removed in the presence of interfering ions (20-100 mg/L). The adsorbent (Fe3O4/FMO) could also be reused up to 4 times with a percentage Cr(VI) removal of > 80 % in the 4th cycle. Adsorption kinetics studies obeyed pseudo second-order model, suggesting a chemical interaction mechanism (chemisorption) between Fe3O4/FMO and Cr(VI). Therefore, the adsorbent has shown that it can be used for selective removal of Cr(VI) from wastewater and potentially other heavy metals as well.